2018
DOI: 10.6061/clinics/2018/e651s
|View full text |Cite
|
Sign up to set email alerts
|

Survival and prognosis of young adults with gastric cancer

Abstract: OBJECTIVES:Survival data for young adults (YA) with gastric cancer is conflicting and scarce in Brazil. The aim of this study was to compare the clinicopathological factors and survival rates of younger and older patients with gastric cancer.METHODS:Hospital registries for 294 gastric cancer patients from a reference cancer hospital in São Paulo, Brazil, were consulted for the retrieval of clinicopathological information and follow-up time. Patients were placed into the following groups: YA (≤40 years; N=71), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 28 publications
3
26
0
6
Order By: Relevance
“…This significant difference in gender disparity is unclear, but likely has a component of exposure in addition to genetics. Of note, we found that females had a slightly better OS compared to their male counterparts, as observed in several other population based studies [4,5,15].…”
Section: Discussionsupporting
confidence: 90%
“…This significant difference in gender disparity is unclear, but likely has a component of exposure in addition to genetics. Of note, we found that females had a slightly better OS compared to their male counterparts, as observed in several other population based studies [4,5,15].…”
Section: Discussionsupporting
confidence: 90%
“…Likely also related to therapeutic advances are the improvements in survival among AYAs with lung, liver, pancreas, and stomach carcinomas (more prominent in males) [ 64 , 65 , 66 , 67 ]. Nevertheless, survival outcomes for these cancers in AYAs have remained relatively poor (<60%), which is characteristic for these cancer types regardless of patient age [ 52 , 68 , 69 , 70 , 71 , 72 ]. Studies focusing on young patients (not necessarily AYAs), have shown that younger patients (aged < 50 years) with lung, liver, pancreas, and stomach carcinomas are more often diagnosed with more aggressive disease with higher grade, more advanced stage and higher metastatic rates when compared with older populations [ 64 , 65 , 68 , 69 , 70 , 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, survival outcomes for these cancers in AYAs have remained relatively poor (<60%), which is characteristic for these cancer types regardless of patient age [ 52 , 68 , 69 , 70 , 71 , 72 ]. Studies focusing on young patients (not necessarily AYAs), have shown that younger patients (aged < 50 years) with lung, liver, pancreas, and stomach carcinomas are more often diagnosed with more aggressive disease with higher grade, more advanced stage and higher metastatic rates when compared with older populations [ 64 , 65 , 68 , 69 , 70 , 71 , 72 ]. This likely relates in part to delays in diagnosis and higher frequencies of driver mutations (e.g., EGFR and ALK mutations in lung cancer patients) [ 72 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…An electronic search of PubMed was performed from January 2000 to October 2019 to identify studies that compared the clinicopathological characteristics of young and older patients with GC, and the age cut-off was limited to 40. A total of 19 studies were included [2,4,5,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67], from which we can draw the following characteristics of GCYA (Table 2): 6.1. A Higher Prevalence in Females.…”
Section: Clinicopathogical Characteristicsmentioning
confidence: 99%